The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.2478/hepo-2019-0008
|View full text |Cite
|
Sign up to set email alerts
|

Eugenia aromaticaO. Berg andAfromomum meleguetaK. Schum botanical entomocides as possible synergetic protectant againstCallosobruchus maculatus(Fabricus) (Coleoptera: Chrysomelidae) infestation on stored cowpea (Vigna unguiculata(L.) Walp.)

Abstract: Summary Introduction: Post-harvest protection of food grains against stored products insects’ infestation is a complementary means towards ensuring food security. Objective: Powders and extracts from Eugenia aromatica O. Berg and Aframomom melegueta K. Schum are to be evaluated for their synergetic effects on Callosobruchus maculatus Fabricus under laboratory conditions. Methods: The products were applied at rates of 1 g/20 g and 1% conc./20 g cowpea seeds respectively. Results: Findings show that E. aromatica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Grain protectants play vital role in extending the storability of seeds to longer duration without appreciable loss in vigor and viability (Adesina et al 2019a). The findings obtained in this study showed that S. afzelii extracts are effective as stored grains protectant against storage insects in reducing grain damage and ultimately lower weight loss.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Grain protectants play vital role in extending the storability of seeds to longer duration without appreciable loss in vigor and viability (Adesina et al 2019a). The findings obtained in this study showed that S. afzelii extracts are effective as stored grains protectant against storage insects in reducing grain damage and ultimately lower weight loss.…”
Section: Discussionmentioning
confidence: 57%
“…The effect of S. afzelii extracts on germination of treated wheat samples was determined following the method of Adesina et al (2019a). Damaged and undamaged grains carefully separated, 20 g of wheat grains in each of the fumigated and contact toxicities groups were randomly selected from the undamaged ones and placed on moistened tissue paper in sterilized Petri plates as the growth medium and allowed to germinate at room temperature.…”
Section: Seed Germination Testmentioning
confidence: 99%
See 1 more Smart Citation